Visual Representation Analysis of Meaning in BJB Bank and HSBC Bank Advertisements - Sari, Vitcha; Hamzah, Hamzah (Universitas Negeri Padang, 2021)
This study aims to examine the difference of meaning in visual analysis in BJB Bank and HSBC Bank advertisements. The purpose of this research is to find the difference in meaning in the visual analysis of Kress and Leeuwen metafunction, namely representational, interactional, and compositional. The data were analyzed using the theory of grammar of visual design Kress and Leeuwen (1996). The data is the visual contained in the BJB bank and the HSBC bank advertisement videos. The method of this research uses descriptive qualitative research. The results showed some differences in BJB bank and HSBC bank advertisements in visuals which are a narrative reactional phenomenon and conceptual, symbolic attribute in representational, equality in interactional, and foregrounding and backgrounding in compositional.